Nigella sativa powder for helicobacter pylori infected patients: a randomized, double-blinded, placebo-controlled clinical trial - Hedieh Yousefnejad; Farzaneh Mohammadi; Mahvash Alizadeh-naini; Najmeh Hejazi (BMC, 2023)
Abstract Objective This double-blind, placebo-controlled, clinical trial was conducted to define the effects of Nigella sativa (N. Sativa) powder plus conventional medical treatment of Helicobacter pylori (H. pylori) on serum ghrelin level and appetite in H. pylori-infected patients. Methods In the present study, 51 H. pylori-positive patients were randomly allocated to treatment (n = 26) or placebo (n = 25) groups. They received 2 g/day N. Sativa with quadruple therapy or 2 g/day placebo plus quadruple therapy for 8 weeks. The serum level of ghrelin was assessed before and after the intervention. Appetite was evaluated at the onset and at the end of the intervention. Results At the end of the study, the appetite of the treatment group improved significantly compared with the placebo group (P = 0.02). Statistically, the difference in serum ghrelin levels between the study's groups was insignificant (P > 0.05). Conclusion Supplementation with N. Sativa powder may be a beneficial adjunctive therapy in H. pylori-infected patients. Trial registration This study was registered in the Iranian Registry of Clinical Trials (IRCT20170916036204N7) on 08/08/2018.